Approximation algorithms for time constrained scheduling - Jansen, Klaus; Öhring, Sabine (1995)
Abstract: "In this paper we consider the following time constrained scheduling problem. Given a set of jobs J with execution times e(j)[belonging to] (0,1] and an undirected graph G = (J, E), we consider the problem to find a schedule for the jobs such that adjacent jobs (j, j') [belonging to] E are assigned to different machines and that the total execution time for each machine is at most 1. The goal is to find a minimum number of machines to execute all jobs under this time constraint. This scheduling problem is a natural generalization of the classical bin packing problem. We propose and analyse several approximation algorithms with constant absolute worst case ratio for graphs that can be colored in polynomial time."
Keywords: Datenverarbeitung; Constraint programming (Computer science); Electronic data processing -- Distributed processing; Graph theory; Scheduling